2022
DOI: 10.3390/ma16010179
|View full text |Cite
|
Sign up to set email alerts
|

Green and Superior Adsorbents Derived from Natural Plant Gums for Removal of Contaminants: A Review

Abstract: The ubiquitous presence of contaminants in water poses a major threat to the safety of ecosystems and human health, and so more materials or technologies are urgently needed to eliminate pollutants. Polymer materials have shown significant advantages over most other adsorption materials in the decontamination of wastewater by virtue of their relatively high adsorption capacity and fast adsorption rate. In recent years, “green development” has become the focus of global attention, and the environmental friendli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 267 publications
0
1
0
Order By: Relevance
“…Liu et al pointed out that the poor environmental tolerance of Sphingomonas sp., the high viscosity and weak acidity resulting from welan gum accumulation, and the pigments produced during carotenoid synthesis lead to the high energy consumption and costs of polysaccharide purification (Liu et al 2020). Ge et al found that the pigment adsorption capacity of welan gum is pH-dependent, with acidic conditions favoring pigment adsorption (Ge et al 2022). While studying welan gum/graphene oxide nanocomposite hydrogels, Yu et al discovered that welan gum has excellent pigment adsorption ability, which indicates its weak ability to remove carotenoids (Yu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al pointed out that the poor environmental tolerance of Sphingomonas sp., the high viscosity and weak acidity resulting from welan gum accumulation, and the pigments produced during carotenoid synthesis lead to the high energy consumption and costs of polysaccharide purification (Liu et al 2020). Ge et al found that the pigment adsorption capacity of welan gum is pH-dependent, with acidic conditions favoring pigment adsorption (Ge et al 2022). While studying welan gum/graphene oxide nanocomposite hydrogels, Yu et al discovered that welan gum has excellent pigment adsorption ability, which indicates its weak ability to remove carotenoids (Yu et al 2015).…”
Section: Discussionmentioning
confidence: 99%